Landing kinematics, kinetics and EMG in male and female athletes and non-athletes: implications for ACL injury risk - Smith, D. R.; Bowerman, S.; Jackson, S.; Carlson, M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Female athletes are more likely to sustain an ACL injury than male athletes. The purpose was to investigate variables that have been identified as ACL risk factors during a landing task to determine differences among male and female athletes and non-athletes (N = 100). Variables included knee angle at contact, maximum knee angle, time (contact to max angle), VGRF, and muscle activation. Male non-athletes bent the knees significantly more after contact than male athletes. Male athletes landed with significantly more force per body weight than male non-athletes or female athletes and male non-athletes landed with significantly more force than female non-athletes. No other significant differences were observed. The authors concluded that the high rate of ACL injury among female athletes cannot be explained by the landing strategy employed in a jump.